Evidence-based Program Design: Integrated Science - Symons, Sarah L.; Colgoni, Andrew; Eyles, Carolyn H.; Harvey, Chad T.; Robinson, Sarah J. (My University, 2010)
iSci is an innovative four-year undergraduate program offered by the Faculty of Science at McMaster University. With an intake of fewer than sixty students, a focus on learning by research, and a unique pedagogical model, iSci attracts high-achieving students who want a varied, challeng- ing and integrated science degree.
This poster uses Chickering & Gamson’s “seven principles” (1987) to ex- plore how the iSci instructional team incorporated results from educational research projects into the design of the iSci program: Seven principles for good practice in undergraduate education
Encourages contact between students and faculty
Develops reciprocity and cooperation among students
Encourages active learning
Gives prompt feedback
Emphasizes time on task
Communicates high expectations
Respects diverse talents and ways of learning
Keywords: Science and Mathematics Education; Science and Mathematics Education; iSci